Pengaruh Budaya Organisasi terhadap Kinerja Pegawai dengan Pengembangan Karir sebagai Variabel Intervening - Sri Mulyani; Sulkan Sulkan; Chamariyah Chamariyah (Trending: Jurnal Manajemen dan Ekonomi, 2025)
Sulkan, 2024. The Influence of Organizational Culture on Employee Performance with Career Development as an Intervening Variable. Wijaya Putra University Postgraduate Program Surabaya. This type of research is explanatory research, the approach used is a quantitative approach, the research sample is 92 respondents. The analysis tool uses Smart PLS (Partial Least Square). Research objectives: 1) To describe organizational culture, career development and employee performance at the Pakong Community Health Center, Pamekasan Regency. 2) To test and analyze whether there is a significant influence of organizational culture on employee performance at the Pakong Community Health Center, Pamekasan Regency. 3) To test and analyze whether there is a significant influence of organizational culture on employee career development at the Pakong Community Health Center, Pamekasan Regency. 4) To test and analyze whether there is a significant influence of career development on employee performance at the Pakong Community Health Center, Pamekasan Regency. 5) To test and analyze whether there is a significant indirect influence of organizational culture on employee performance at the Pakong Community Health Center, Pamekasan Regency with human resource competency as an intervening variable. The research results show that: 1) organizational culture has a significant positive effect on employee performance with a p value of 0.000. 2) organizational culture has a significant positive effect on career development with a p value of 0.000. 3) work development on employee performance has a significant positive effect with a p value of 0.000. 4) organizational culture on employee performance through career development has a significant positive effect with a p value of 0.008.